The Digital Medieval Manuscript : Material Approaches to Digital Codicology - Haaren, Suzette van, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
We increasingly encounter medieval books as digital facsimiles-zooming in on high-resolution images, clicking through virtual pages, or engaging with interactive displays. But what actually happens when a parchment manuscript is translated into a digital object? How does this change affect our understanding of cultural heritage? This book explores the digital medieval manuscript as a unique cultural artifact, not just a copy of its physical counterpart. Through three case studies, it reveals how digital manuscripts function in libraries, museums, and scholarship today. Blending manuscript studies with digital humanities, it offers a fresh materialist approach to the discourse surrounding the digitisation of cultural heritage and provides a nuanced view of how it shapes the way we perceive, handle, and preserve medieval manuscripts in an increasingly digital world.